2018
DOI: 10.23939/ctas2018.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials and nanotechnology in water purification.Review

Abstract: Висвітлено останні досягнення та застосування нанотехнологій для очищення стічних вод. Наноматеріали мають високу реакційну здатність і високий ступінь функціоналізації, велику специфічну поверхню, що робить їх придатними для застосування в очищенні стічних вод та для опріснення води. Розглянуто застосування різних наноматеріалів, таких як наночастинки металів, оксиди металів, вуглецеві сполуки, цеоліт, фільтраційні мембрани тощо, у нанофільтрації, адсорбції, розділенні органічних та неорганічних речовин та фо… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Having the similar results in his study, Dach [22] suggested that the rejections of salts increased with the feed pressure and decreased with the salt concentration and recovery rate in case of nanofiltration. Kuntyi et al [24] explained that the characteristics of nanomaterials, like high reactivity and a high degree of functionalization, large specific surface area, are making these suitable for wastewater treatment and desalination of saline water. The results of Tay et al [25] revealed that the NF-MBR achieved superior quality permeate because of biodegradation and high rejection capacity of the NF membrane, leading to lower fouling rates.…”
Section: Discussionmentioning
confidence: 99%
“…Having the similar results in his study, Dach [22] suggested that the rejections of salts increased with the feed pressure and decreased with the salt concentration and recovery rate in case of nanofiltration. Kuntyi et al [24] explained that the characteristics of nanomaterials, like high reactivity and a high degree of functionalization, large specific surface area, are making these suitable for wastewater treatment and desalination of saline water. The results of Tay et al [25] revealed that the NF-MBR achieved superior quality permeate because of biodegradation and high rejection capacity of the NF membrane, leading to lower fouling rates.…”
Section: Discussionmentioning
confidence: 99%